From status inconsistency to revisionism: Russian foreign policy after color revolutions. (1st August 2018) - Mazloomi, Esmaeil; Yeoh, Emile Kok-Kheng; Karim, Mohd Aminul
Abstract: This paper delves into the shifts in the foreign policy of Russia, considering what has determined Russia's grand strategy orientation after the collapse of the Soviet Union. It also attempts to offer an explanation of why Russia becomes discounted with the 'constitutive and normative structure', and how its foreign policy shifted toward the anti-status quo orientation, especially after the color revolutions. The main purpose of this paper is to explain the shift in Russia's foreign policy, from the search for the 'greatpowerness' status via different enhancement strategies in light of status quo in the 'revolutionary decade', to revisionism after the color revolutions in Commonwealth of Independent States region (2003–2005). To substantiate this, the study uses process-tracing and document analysis to show the changes in Russia's foreign policy. As demonstrated in this paper, power rendered is unable of directing or disinclined to direct its policies toward status quo, due to internal effects of perceived 'status immobility' resulting from the failure of several status enhancement strategies. Accordingly, the shift in Russia's foreign policy was a result of changing the Russian perception from status inconsistency to status immobility.